An Experience with Intravitreal Dexamethasone Implant for Uveitic Macular Oedema - Kharel (Sitaula), Ranju; Shrestha, Saurav Man (Journal of Nepal Health Research Council, 2021)
Intravitreal steroid implants are the latest trend for uveitis macular oedema treatment. Dexamethasone intravitreal implants are new in our contexts but we report 2 cases of uveitic cystoid macular oedema where this implant proved very useful in the treatment of recalcitrant macular oedema where other treatment modality fails. Two cases of non-infectious uveitis and intermediate uveitis with recalcitrant uveitic macular oedema underwent dexamethasone intravitreal implantation. Their central macular thickness & central macular volume reduced significantly with the implant. With the reduction in macular parameters, the best-corrected visual acuity also improved and visual rehabilitation was achieved. Thus, dexamethasone intravitreal implant helps in sustained drug delivery inside the vitreous leading to resolution of uveitic macular oedema in recalcitrant cases. Keywords: Macular oedema; ozurdex; steroid; uveitis; vision